The Impact of Continuous Integration and Continuous Delivery on Software Development Efficiency - Yang, Shuai (Journal of Computer, Signal, and System Research, 2025)
This paper explores the impact of Continuous Integration (CI) and Continuous Delivery (CD) on software development efficiency. By examining the core principles, practices, and benefits of CI/CD, the study highlights how these practices contribute to faster development cycles, improved code quality, and enhanced collaboration across development teams. The paper discusses the challenges organizations face when implementing CI/CD, such as tool selection, cultural resistance, and security concerns, and provides practical recommendations for overcoming these obstacles. Additionally, it offers insights into future research directions, including the integration of AI in CI/CD processes, CI/CD implementation in multi-cloud environments, and enhancing security within CI/CD pipelines. The findings underscore the transformative role of CI/CD in modern software development and its potential for driving continuous improvement.